Prevention of traffic accidents through the moral knowledge approach in upper secondary students - Hariyati, Hariyati; Palilati, Alida; Ngii, Edward; Putra, Adris Ade (Edelweiss Applied Science and Technology, 2024)
Road traffic accidents that are very high among students can be overcome by instilling Moral Knowledge or Moral Knowledge, which is an important thing to teach. If students already know morals, they will have moral awareness which will be embedded consistently between knowledge and actions (moral action). This type of research is qualitative descriptive, in-depth interviews and questionnaires carry out the data collection method. The results showed that students’ moral knowledge related to traffic ethics on the road had not been fully formed. The stages that can be done in understanding moral knowledge in students to reduce the number of traffic accidents among students are moral awareness so that students can distinguish between right and wrong actions or perceptions, prohibitions and recommendations, and good or bad behavior. Second, character education to foster habits (Habitation) towards noble moral values. Third, moral action is to practice noble moral values in daily behavior.